2022
DOI: 10.3390/jpm12081310
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Importance to Patients in Reproductive Genetic Carrier Screening: A Qualitative Study to Inform a Core Outcome Set

Abstract: There is significant heterogeneity in the outcomes assessed across studies of reproductive genetic carrier screening (RGCS). Only a small number of studies have measured patient-reported outcomes or included patients in the selection of outcomes that are meaningful to them. This study was a cross-sectional, qualitative study of 15 patient participants conducted to inform a core outcome set. A core outcome set is an approach to facilitate standardisation in outcome reporting, allowing direct comparison of outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Previous work highlights patient perceptions that reproductive empowerment most accurately captures the utility of RGCS. 18,19 Empowerment considers behaviour in the wider context of cognitive capacity, knowledge and emotional state. 7 Building on these patient-derived ndings, the participants in the study reported here perceived utility as a multifaceted concept requiring the assessment of multiple relevant outcomes encompassing broad societal impact (disease incidence or number of affected births), speci c actions (reproductive decisions made by increased risk couples) and the patient perspective (feeling empowered to make reproductive decisions that align with patient values).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work highlights patient perceptions that reproductive empowerment most accurately captures the utility of RGCS. 18,19 Empowerment considers behaviour in the wider context of cognitive capacity, knowledge and emotional state. 7 Building on these patient-derived ndings, the participants in the study reported here perceived utility as a multifaceted concept requiring the assessment of multiple relevant outcomes encompassing broad societal impact (disease incidence or number of affected births), speci c actions (reproductive decisions made by increased risk couples) and the patient perspective (feeling empowered to make reproductive decisions that align with patient values).…”
Section: Discussionmentioning
confidence: 99%
“…Patient participants were identi ed from previous stakeholder consultations in which co-design methods were used to elicit outcomes of importance to patients and had provided consent to be approached for the Delphi survey. 19 Health professional participants were identi ed by the rst and last authors of publications included in our sequential systematic review 17,18 , listed committee members from key policy and practice recommendations, and through professional networks within AUS/NZ.…”
Section: Participant Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Consultations with patient stakeholders further re-iterated the importance of these patient-led outcomes as a focus for future research. 19 A consensus process through which all collated outcomes from previous steps are reviewed, refined and prioritised by key stakeholders is the culmination of a core outcome development study. The goal of this process is to determine which outcomes are the most important to define as core outcomes that should be reported in all future studies on RGCS.…”
Section: Introductionmentioning
confidence: 99%